Schoolyard stories: Processes of gender identity in a ‘children’s place’. - Rönnlund, Maria (Childhood, 2015)
Drawing on data from a Swedish primary school, this article explores how the schoolyard and places within the schoolyard are discursively used in processing gender identity. The analysis of children’s narratives in relation to four identified key places indicated diverse and parallel ways of processing gender identity, and that spatial characteristics formed different conditions for processing gender identity. The analysis stresses the importance of understanding gender identity as spatial and diverse and children as active agents in processing this identity. Following the analysis outlined in the article, it is argued that a spatially diverse and multi-characteristic schoolyard is likely to meet various and parallel ways of processing gender identity to a greater extent than a schoolyard with low spatial variety. In general, representations of an ‘active’, ‘playing with everybody’, ‘rule-abiding’, and ‘gendered’ school child were not challenged to any great extent. This result indicates the power of institutional and societal forming and framing in contemporary outdoor school environments.